2018
DOI: 10.1016/j.virol.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of safety and immunogenicity of the Chinese Hu191 measles virus vaccine by alteration of the S-adenosylmethionine (SAM) binding site in the large polymerase protein

Abstract: The live-attenuated measles virus (MV) vaccine based on the Hu191 strain has played a significant role in controlling measles in China. However, it has considerable adverse effects that may cause public health burden. We hypothesize that the safety and efficacy of MV vaccine can be improved by altering the S-adenosylmethionine (SAM) binding site in the conserved region VI of the large polymerase protein. To test this hypothesis, we established an efficient reverse genetics system for the rMV-Hu191 strain and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
(69 reference statements)
1
14
0
Order By: Relevance
“…Viruses lacking mRNA cap ribose 2 0 -O methylation will make the virus more easily recognized by host cells, activate the interferon system and then promote T cell immune response and B cell immune response and improve immunogenicity. This finding has been proven in several NNS RNA viruses, including measles virus (MV), human metapneumovirus (hMPV), avian metapneumovirus (aMPV), rabies virus (RABV) and vesicular stomatitis virus (VSV) (Ma et al 2014;Sun et al 2014;Zhang et al 2014;Wang et al 2018). These studies showed that recombinant viruses lacking MTase activity were highly attenuated both in vitro and in vivo yet retained high immunogenicity.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Viruses lacking mRNA cap ribose 2 0 -O methylation will make the virus more easily recognized by host cells, activate the interferon system and then promote T cell immune response and B cell immune response and improve immunogenicity. This finding has been proven in several NNS RNA viruses, including measles virus (MV), human metapneumovirus (hMPV), avian metapneumovirus (aMPV), rabies virus (RABV) and vesicular stomatitis virus (VSV) (Ma et al 2014;Sun et al 2014;Zhang et al 2014;Wang et al 2018). These studies showed that recombinant viruses lacking MTase activity were highly attenuated both in vitro and in vivo yet retained high immunogenicity.…”
Section: Introductionmentioning
confidence: 82%
“…In this study, we used BHK cells stably expressing T7 RNA polymerase to rescue rMuVs, which prevents the risk of being contaminated by vaccinia virus. This method has been approved in other studies for rescue of human metapneumovirus, bovine respiratory syncytial virus and measles virus (Ma et al 2014;Sun et al 2014;Zhang et al 2014;Cui et al 2017;Pang et al 2018;Wang et al 2018;Zhou et al 2019b). We have effectively rescued rMuV-S79 without helper vaccinia virus in our previous researches (Zhou et al 2019a(Zhou et al , 2019b.…”
Section: Discussionmentioning
confidence: 99%
“…In this research, full-length cDNA clone of MuV-S79 was constructed using a novel plasmid assemble strategy which restriction and ligation were not needed for generating plasmid in the assembly process by using a GeneArt™ High-Order Genetic Assembly System. Based on this novel assembly system, full-length genomic clone of measles virus has been generated in our previous research [20].…”
Section: Discussionmentioning
confidence: 99%
“…The strategy to construct the supporting plasmids of pT7-MuV-S79-NP, pT7- MuV-S79-P, and pT7-MuV-S79-L using “seamless” cloning had showed in the previous study [12, 20, 21]. The sequence of primers used in the PCR assays is available on request.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation